The Influence Of Digital Literacy Based On Bima's Local Wisdom On The Critical Thinking Ability Of Classroom Students Viii 10 At SMPN 1 Woha - Fajrun fajrun; Suharti Suharti; Lisda Ramdhani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effect of digital literacy based on Bima local wisdom on students’ critical thinking skills in Grade VIII 10 at SMPN 1 Woha in the Informatics subject. The background of this research is the low ability of students to critically analyze digital information. The research method employed was a Pre-Experimental Design with the form of One Group Pretest-Posttest Design. The research subjects consisted of 29 students selected through purposive sampling. The research instrument was a critical thinking skills test constructed based on Facione’s (2015) indicators, including interpretation, analysis, evaluation, inference, and explanation. The instrument was validated by three experts, consisting of two subject matter experts and one educational evaluation expert, who confirmed that the test items were suitable for use. The research procedure consisted of three stages: (1) pretest, to measure students’ initial critical thinking skills; (2) treatment, namely digital literacy learning based on Bima local wisdom in the Informatics subject integrating cultural values with digital content; and (3) posttest, to measure the improvement of critical thinking skills after the treatment.The results showed a significant improvement in students’ critical thinking skills after the treatment. The mean score increased from 44.48 in the pretest to 82.06 in the posttest, with a difference of 37.58 points. The Wilcoxon test result indicated Asymp. Sig. (2-tailed) = 0.000 (<0.05), confirming a significant difference between pretest and posttest scores. The effect size calculation using Cohen’s d = 2.66 indicated that the treatment had a very large effect. Pedagogically, this study confirms the effectiveness of integrating digital literacy with local wisdom in enhancing students’ critical thinking skills. Culturally, it contributes to the preservation of Bima’s local values. However, this study is limited by a small sample size, non-normal data distribution, and a relatively short duration of the learning intervention. Future research is recommended to involve larger and more diverse samples, employ control groups, and apply longitudinal designs to assess long-term effects. This study suggests that schools and teachers should develop culturally grounded digital-based learning models as a strategy to strengthen 21st-century skills while reinforcing students’ cultural identity.